2019
DOI: 10.1002/jcop.22203
|View full text |Cite
|
Sign up to set email alerts
|

School‐wide implementation of positive behavioral interventions and supports in an alternative school setting: A case study

Abstract: AimsThe purpose of this 1‐year case study was to identify how School‐Wide Positive Behavioral Interventions and Supports (SW‐PBIS) can be adapted to meet the needs of students in alternative schools and to evaluate the early impact of SW‐PBIS on discipline outcomes.MethodsSuggestions for adaptations are provided at each stage of the intervention process with a focus on buy‐in, training, data collection, and resource allocation.ResultsData from this case study included information about key components of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The term "alternative school" has been used to describe many different types of school settings. Generally, an alternative school is defined as a "school designed to provide specialized instruction to students who require more intensive support than can be offered in a traditional school" (Griffiths et al, 2019(Griffiths et al, , p. 1495. The National Center for Education Statistics (NCES; 2017) defines an alternative education (AE) school as, "A public elementary/secondary school that (1) addresses needs of students that typically cannot be met in a regular school, (2) provides nontraditional education, (3) serves as an adjunct to a regular school, or (4) falls outside the categories of regular, special education, or vocational education."…”
Section: Alternative School Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "alternative school" has been used to describe many different types of school settings. Generally, an alternative school is defined as a "school designed to provide specialized instruction to students who require more intensive support than can be offered in a traditional school" (Griffiths et al, 2019(Griffiths et al, , p. 1495. The National Center for Education Statistics (NCES; 2017) defines an alternative education (AE) school as, "A public elementary/secondary school that (1) addresses needs of students that typically cannot be met in a regular school, (2) provides nontraditional education, (3) serves as an adjunct to a regular school, or (4) falls outside the categories of regular, special education, or vocational education."…”
Section: Alternative School Settingsmentioning
confidence: 99%
“…Given a primary purpose of the alternative school settings to provide specialized instruction to students (Griffiths et al, 2019), particularly with disruptive behaviors (Foley & Pang, 2006), it seems only natural that there needs to be additional literature targeting the use of behavioral interventions in these settings. The landscape of the current literature focusing on behavioral interventions in alternative school settings is limited and haphazard, with a definite need for increased attention and direction.…”
Section: Behavior Interventionsmentioning
confidence: 99%
“…Integration of universal, Tier 1 practices within AE settings could potentially improve the efficiency and effectiveness of behavioral supports while also increasing opportunities for flexible staffing options. Implementation of Tier 1 PBIS in AE settings has been shown to increase on-task and prosocial behaviors, decrease problem behaviors, and decrease staff use of restraint and seclusion procedures (Farkas et al, 2012; Grasley-Boy et al, 2021; Griffiths et al, 2019; Simonsen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research suggests that PBIS can be adapted within AE settings to effectively support the social–emotional and behavioral needs of students with significant disabilities. More specifically, implementation of Tier 1 PBIS within AE settings has been associated with increases in on-task and prosocial behaviors, along with decreases in problem behaviors such as defiance and physical aggression ( Farkas et al, 2012 ; Griffiths et al, 2019 ; Simonsen et al, 2010 ). Results of a recent systematic review of 19 studies conducted by Grasley-Boy and colleagues (2021) indicated that use of restraint and seclusion procedures following implementation of PBIS within AE settings almost always decreased and continued on a decreasing trend over multiple years when evaluated over time.…”
Section: Alternative Education Settingsmentioning
confidence: 99%
“…Research in this area is complicated by the fact that districts use diverse terms to describe alternative schools, such as “transfer” schools in New York City or “options” schools in Chicago and Los Angeles. There is no agreed-upon national standard defining the components of a successful alternative education program or how they should be evaluated for effectiveness (Duffield, 2018; Griffiths et al, 2019; McGee & Lin, 2017). In 2008, a national survey reported that 646,500 students in the United States attended alternative schools; 64% of surveyed districts had an alternative school or program (Carver et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%